2004
DOI: 10.21236/ada607046
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Chromium Electroplating on Landing Gear Components Using HVOF Thermal Spray Coatings

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
0
18
1
Order By: Relevance
“…An integrated approach is adopted that includes the response to corrosion (potentiodynamic, potentiostatic polarization) and sliding wear, as well as an insight into the mechanisms involved. The motivation behind this work lies upon the following facts: (a) the limited research works on the wear and, especially, corrosion behaviour of nanostructured hard metal coatings on light metal alloys; (b) the need to improve the tribological and corrosion behaviour of light metal alloys; (c) the need to expand the use of aluminium alloys to engine design for reducing fuel consumption and other corrosion/wear resistant applications (e.g., cylinder liners [56], cylinder heads [57], cylinder bore walls [58], turbojet engine blade roots and edges [59], aircraft flap tracks [60], fan and compressor blade mid-span dampers [61], plastic injection moulds [50]); and(d) the necessity to replace electrolytic hard chromium plating (due to carcinogenic Cr(VI) emissions) with environmentally friendlier techniques, such as HVOF.…”
Section: Introductionmentioning
confidence: 99%
“…An integrated approach is adopted that includes the response to corrosion (potentiodynamic, potentiostatic polarization) and sliding wear, as well as an insight into the mechanisms involved. The motivation behind this work lies upon the following facts: (a) the limited research works on the wear and, especially, corrosion behaviour of nanostructured hard metal coatings on light metal alloys; (b) the need to improve the tribological and corrosion behaviour of light metal alloys; (c) the need to expand the use of aluminium alloys to engine design for reducing fuel consumption and other corrosion/wear resistant applications (e.g., cylinder liners [56], cylinder heads [57], cylinder bore walls [58], turbojet engine blade roots and edges [59], aircraft flap tracks [60], fan and compressor blade mid-span dampers [61], plastic injection moulds [50]); and(d) the necessity to replace electrolytic hard chromium plating (due to carcinogenic Cr(VI) emissions) with environmentally friendlier techniques, such as HVOF.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among the results of such research activities, it has been shown that WC-Co base coatings deposited by high velocity oxygen fuel (HVOF) are good candidates for such a purpose, particularly for the successful replacement of EHC in aeronautical and aerospace applications. [2][3][4][5][6][7][8] HVOF WC-Co base cermets can withstand high contact pressures without spallation and are often used in applications where abrasive wear and erosion resistance are of a primary concern, whereas WC-Co-Cr base coatings are preferred when a higher corrosion resistance is required.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results of literature studies showed that this type of coatings had good wear and corrosion resistant properties [12-14]. Low porosity (1%), low oxidation (1%) and a significantly lower harmful effect on the ecosystem [15,16] are the reasons for using WC–20Co–1Ni HVOF-sprayed coating for hard chromium replacement. In this study, the feasibility of replacing the WC–20Co–1Ni coating by HVOF using the hard chromium coating plating on the rotor and its consequences on the lifespan and performance of the downhole drilling motor was examined.…”
Section: Introductionmentioning
confidence: 99%